First Record of Three Pleuromamma Species (Copepoda: Calanoida: Metridinidae) in Korea. - Jeong, H.G., S.J. Lee & H.Y. Soh (Animal Systematics Evolution and Diversity, 2022)
Three Pleuromamma copepods were newly collected from the South Sea of Korea in the summer when the Tsushima Warm Current was strong. They were identified as Pleuromamma abdominalis (Lubbock, 1856), P. indica Wolfenden, 1905, and P. xiphias (Giesbrecht, 1889). Although these species have been reported in world oceans, they were first reported from Korean waters. So far, four species of Pleuromamma (P. borealis Dahl, 1893, P. gracilis Claus, 1863, P. piseki Farran, 1929, and P. robusta (Dahl, 1893)) have been recorded in Korean waters. We provided re-description of these three species insufficiently described by previous authors and key characters for species identification in addition to species hitherto known in Korea.